Analisis Keadilan dalam Izin Poligami: Perbandingan Putusan Mahkamah Syariah Malaysia dan Pengadilan Agama Indonesia - Jalil Jalil (STIKes Ibnu Sina Ajibarang, 2026)
The principle of justice constitutes the core of debates regarding the permissibility of polygamy in Islamic law; however, the standards used to assess justice in judicial practice still vary between countries. This study comparatively examines how the Malaysian Syariah Court and the Indonesian Religious Court implement the concept of justice as the primary requirement for granting polygamy permits in judicial practice. The research employs a comparative legal approach and normative-juridical analysis of court decisions and statutory regulations applicable in both countries. The findings reveal that although both judicial systems refer to Qur’an Surah An-Nisa verse 3 as the normative foundation, significant differences exist in the mechanisms for proving justice, the consideration of the interests of existing wives, and the role of judges in assessing the feasibility of polygamy applications. Malaysia tends to apply a more structured standard of justice through strict technical regulations, while Indonesia provides broader judicial discretion by considering sociological aspects. Both countries also face similar challenges in translating immaterial justice into objective, consistent, and measurable legal decisions.